Sarasehan “Menyongsong Pemilu Damai 2024” Di Desa Duwet Kecamatan Wonosari Kabupaten Klaten - Abdullah, Mu'in; Fajrin, Rara Intan Mutiara; Fathurrohman, Mukhlis (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
General elections have become a global phenomenon. Elections are the best way to ensure a peaceful transition of power. Election practices throughout the world vary in how they are carried out but remain based on honest, free, fair and peaceful elections. The political year gave rise to conflict between communities and even social strife caused by differences in decisions and opinions between communities, so the aim of this activity is to educate the public about peaceful elections packaged in a national insight workshop. This activity was carried out in Duwet village, Wonosari District, Klaten Regency. This activity used the lecture and workshop method or question and answer. In the lecture method, material on national insight will be presented and at the workshop time will be provided for question and answer discussions about national insight. The results of the implementation of community service show that the community increasingly understands the meaning of nationality as an encouragement to welcome the 2024 elections that are honest, free, fair and peaceful, understand the meaning of togetherness, respect each other and respect each other's differences in choices.